Isolation of suberin from birch outer bark and cork using ionic liquids: A new source of macromonomers (Industrial Crops and Products, 2012)
Cholinium hexanoate, a biocompatible and biodegradable ionic liquid, was recently demonstrated to efﬁciently and selectively extract suberin domains from cork, combining high extraction efﬁciency with isolation of a partial depolymerised material. In the present paper, we report a comparative study of the characterisation of suberin extracted from birch outer bark and from cork using cholinium hexanoate. It became apparent that both extracted suberin samples showed still a cross-linked nature, i.e. likely to be closely related to in situ suberin. Suberin samples were mainly constituted by oligomeric or polymeric structures in turn essentially composed by long chain hydroxyacids monomers. Their high thermal stability together with the oligomeric/polymeric nature, open new perspectives for suberin use as macromonomers in the development of bio-based polymeric materials. This also contributes for the valorisation of suberin rich agro-forest residues.

Dissolution of cork biopolymers in biocompatible ionic liquids - Garcia, Helga; Ferreira, Rui; Petkovic, Marija; Ferguson, Jamie L.; Leitão, Maria C.; Gunaratne, H. Q. Nimal; Seddon, Kenneth R.; Rebelo, Luís Paulo N. Luis Paulo N.; Silva Pereira, Cristina; Leitão, Maria C. (Green Chemistry, 2010)
Classically, the best attempts to separate suberin from cork biopolymers have resulted in low efficiency; here, we report a class of biocompatible and biodegradable cholinium-based ionic liquids, the cholinium alkanoates, which show a highly efficient and specific dissolution of the suberin domains from cork biopolymers.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Cork; cork biopolymers dissolution; ionic liquids; suberin (voyant)